A autobiografia como metodologia para uma história da disciplina arte no Brasil vida e formação de uma arte/educadora - Lanzi, Lucirene Andréa Catini (Editora Oficina Universitária, 2022)
Taking as a premise that from the experiences of each educator it is possible to make intersections with the training history of other professionals in the area; and from these similarities it is possible to glimpse aspects that are present in the very history of the subject they teach and that this work is developed. In this way, it is questioned whether the experience of becoming an art/educator contributes to understanding the teaching of Art in Brazil? In this sense, we propose an analysis of aspects of the author's life and education as an art/educator for the study of the Art discipline in Brazil. Such aspects can be collected from what we currently know as Early Childhood Education, in which teachers who recognize the importance of the child's creative act and offer possibilities to envision the school space and the discipline of Art as a cultural action, can influence the formation of the art/educator. . In the end, through the researcher's autobiographical reports, they go beyond individual limits and assume a meaning that can be extended to a community of subjects who share similar experiences and, in this sense, working with autobiographical memory can mean an important contribution to the history of teaching. . LEONARDO MARQUES TEZZA